2014
DOI: 10.1186/1471-2164-15-s9-s8
|View full text |Cite
|
Sign up to set email alerts
|

Homopharma: A new concept for exploring the molecular binding mechanisms and drug repurposing

Abstract: BackgroundDrugs that simultaneously target multiple proteins often improve efficacy, particularly in the treatment of complex diseases such as cancers and central nervous system disorders. Many approaches have been proposed to identify the potential targets of a drug. Recently, we have introduced Space-Related Pharmamotif (SRPmotif) method to recognize the proteins that share similar binding environments. In addition, compounds with similar topology may bind to similar proteins and have similar protein-compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…On the basis of the results above, we considered the idea that CHRNB4 could be a potential therapeutic target for the inhibition of migration and invasion in smoking HNSCC patients. By using in-house methods and tools (Homopharma and iGEMDOCK) [60,73,74], we discovered an FDA-approved drug, called varenicline, as a potential CHRNB4 inhibitor (purchased from Sigma-Aldrich, #PZ0004). We utilized parental cell lines (FaDu and SCC25) and NNK-treated cell lines to examine the efficacy of the inhibition of migration and invasion by treating cells with varenicline at concentrations of 0, 0.1, 1, and 5 µM (Figure 8 and Data S5).…”
Section: Varenicline As a Repurposing Drug Of Chrnb4 Inhibited Migrmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the results above, we considered the idea that CHRNB4 could be a potential therapeutic target for the inhibition of migration and invasion in smoking HNSCC patients. By using in-house methods and tools (Homopharma and iGEMDOCK) [60,73,74], we discovered an FDA-approved drug, called varenicline, as a potential CHRNB4 inhibitor (purchased from Sigma-Aldrich, #PZ0004). We utilized parental cell lines (FaDu and SCC25) and NNK-treated cell lines to examine the efficacy of the inhibition of migration and invasion by treating cells with varenicline at concentrations of 0, 0.1, 1, and 5 µM (Figure 8 and Data S5).…”
Section: Varenicline As a Repurposing Drug Of Chrnb4 Inhibited Migrmentioning
confidence: 99%
“…Primarily, we systematically integrated the genomic and clinical data of HNSCC patients ( Figure 1) and found neuronal acetylcholine receptor subunit beta-4 (CHRNB4), a kind of nAChR, whose gene expression was upregulated and associated with adverse prognosis in smoking patients. Furthermore, on the basis of our previous work and drug repurposing approach, "Homopharma" [60], we discovered that an FDA-approved smoking cessation agent, varenicline, inhibits CHRNB4 in long-term NNK-treated HNSCC cells. Our results indicate that CHRNB4 is able to determine whether patients who smoke have a favourable or adverse prognosis and that the invasion and migration of NNK-treated cells were decreased when CHRNB4 was inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of genomic medicine, it is possible that some approved drug molecules can be used for diseases other than those they were originally approved for. Yang and co-workers [ 23 ] propose the concept of "Homopharma", to combine similar drug binding environments to better understand molecular binding mechanisms for deploying approved drugs for other diseases, known as "repurposing." Tyagi et al [ 24 ] have optimized arylthioindole compounds for efficiently disrupting tubulin assembly towards anti-cancer therapy, using QSAR and molecular dynamics approaches.…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…Using the homopharma concept, the topology and chemical functional group of an active compound that is similar to an active molecule would bind to the same target protein at the specific binding site. Previous studies have revealed the advantage and success of this technique in the search for new inhibiting mechanisms of known drugs for drug repurposing [36]. Moreover, there is also the ability to use the approach to predict the target of an active compound, which is one of the most critical steps to bridge the gap between experimental and computational studies [37].…”
Section: Introductionmentioning
confidence: 99%